THE USE OF PREPARATIONS MADE FROM SILYBUM MARIANUM GAERTN. L. IN MEDICINE (Konferensiyalar | Conferences, 2024)
Silybum marianum Gaertn. L., commonly known as milk thistle, has been widely used in traditional and modern medicine, primarily for its hepatoprotective properties. Its key bioactive component, silymarin, exhibits strong antioxidant, anti-inflammatory, and detoxifying effects, making it beneficial for liver diseases such as hepatitis, cirrhosis, and fatty liver disease. Furthermore, recent studiessuggest its potential role in diabetes management, cardiovascular health, and even cancer treatment.